Safety and immunogenicity of investigational Shigella conjugate vaccines in Israeli volunteers. - Cohen, D (1996)
The safety and immunogenicity of investigational conjugates, composed of the O-specific polysaccharides of Shigella sonnei and Shigella flexneri type 2a covalently bound to Pseudomonas aeruginosa recombinant exoprotein A (rEPA), were evaluated in 192 Israeli soldiers. None had significant local reactions or fever. Fourteen days after injection, 90% of S. sonnei-rEPA recipients and 73 to 77% of S. flexneri-rEPA recipients had a fourfold or greater increase in serum immunoglobulin G (IgG) and IgA anti-lipopolysaccharide (anti-LPS) levels; at 2 years, these remained higher than at prevaccination (P < 0.01). There was a fourfold or greater increase in IgM anti-LPS in 20% of vaccinees at 2 weeks, but levels returned to prevaccination values at 6 to 12 months. IgG was the highest and most sustained class of LPS antibodies. Reinjection at day 42 did not boost antibody levels. Eighteen of 23 (78%) who received S. sonnei-rEPA and 13 of 19 (68%) who received S. flexneri-rEPA. had significant IgA-secreting cell responses. Significant IgG antibody-secreting cell responses were detected in 19 of 23 (83%) and 11 of 19 (58%) volunteers following vaccination with S. sonnei-rEPA and S. flexneri 2a-rEPA, respectively. On the basis of these data, further evaluation of the Shigella conjugates for protective efficacy in field trials in Israel was started.